Evaluation of a Cognitive Rehabilitation Protocol in HIV Patients with Associated Neurocognitive Disorders: Efficacy and Stability Over Time - Livelli, Alessandro; Orofino, Gian Carlo; Calcagno, Andrea; Farenga, Mariana; Penoncelli, Donatella; Guastavigna, Marta; Carosella, Sinibaldo; Caramello, Pietro; Pia, Lorenzo (Frontiers in Behavioral Neuroscience, 2015)
The primary aim of the present study was to evaluate the efficacy and stability over time of a cognitive rehabilitation protocol (restorative and compensatory approach) in HIV/AIDS patients with HIV-associated Neurocognitive Disorder (HAND). At baseline, thirty-two HIV/AIDS patients (sixteen with and sixteen without HAND) were assessed with a neuropsychological battery (i.e., pre-assessment) consisting of twenty-two tests covering eight cognitive domains. Then, the experimental group was administered over four months a cognitive rehabilitation protocol aimed at improving four cognitive domains by means of eight paper and pencil/computer-based exercises. The control group received guideline-adherent clinical care (i.e., standard of care). At the end of the cognitive treatment, both groups were re-administered the neuropsychological battery (i.e., post-assessment). Additionally, six months after post-assessment, the experimental group was given the same neuropsychological battery (i.e., follow up-assessment). In order to test the efficacy of the cognitive rehabilitation protocol, we compared between groups the results of the neuropsychological battery at the pre- and post- assessments. In order to evaluate the stability over time, the effects of the cognitive rehabilitation protocol was examined comparing within the experimental group the results of the neuropsychological battery at post- and follow up-assessments. Our results show that the two groups did not differ at the pre-assessment, but differed at post- assessment. Specifically, the experimental group showed a significant improvement in five domains (Learning & memory, Abstraction/executive functioning, Verbal fluency, Attention/working memory and Functional), whereas the control group significantly worsened in the same domains. The improvement of the experimental group did not change in the follow up-assessment in two domains (Abstraction/executive functioning, Attention/working memory and Functional). Overall, these findings support the efficacy and, to some extent, the stability over time of our cognitive rehabilitation protocol.